A Cyan Emitting CsPbBr3 Perovskite Quantum Dot Glass with Bi Doping. (16th November 2020) - Zhu, Yuxuan; Yang, Bobo; Lu, Qing; Li, Yang; Shi, Mingming; Zou, Jun
Abstract : CsPbBr3 :xBi 3+ quantum dot glass was prepared by using traditional melting-quenching and heat treatment processes. The effects of Bi doing on the sinter of the precursor of glass and the crystalline of the perovskite quantum dot were discussed detailly. By doping Bi2 O3 into the borosilicate glass matrix, the melting temperature was reduced to 900 °C. The tunable emission of CsPbBr3 quantum dots from 523 to 493 nm was achieved with suitable Bi2 O3 doping. Due to the protection of the inorganic glass matrix, the prepared CsPbBr3 quantum dots still exhibit excellent thermal stability after multiple thermal cycles and thermal shocks. This provides a good solution to the problem of poor thermal stability of perovskite quantum dots.